PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING UNTUK MENINGKATKAN KEAKTIFAN BERTANYA DAN HASIL BELAJAR SEJARAH SISWA KELAS XI IIS 1 SMA NEGERI 1 BOYOLALI TAHUN AJARAN 2015/ 2016 - Isnawati, Isnawati; Pelu, Musa; Isawati, Isawati (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
The purpose of this research is to improve students? questioning participation andlearning outcomes of students in class XI IIS 1 SMA Negeri 1 Boyolali by applying learning strategy of active knowledge sharing in history subject.This research is a classroom action research (CAR). The research was conducted in two cycles, with each cycle consisting of a plan, action, observation, and reflection. The subjects were 34 students of class XI IIS 1 SMA Negeri 1 Boyolali. Data source was derived from the teacher, the students and the learning prosess. Data collection techniques were implemented by interviews, conducting tests, observations, and documentation. Testing the data validity was done by using triangulation techniques. Data analysis was conducted by using comparative descriptive analysis techniques. The research model used was the spiral model (Planning, Acting, Observing, and Reflecting).The results showed that the teacher and students are able to apply learning strategy of active knowledge sharing in the learning process, so that the learning process ran well. Teacher's activities in pre-cycle teaching was 63,24% which increased into 75,00% in the first cycle and 91,67% in the second cycle. Students' activities in pre-cycle learning was 59,09% which increased into 77,08% in the first cycle and 93,75% in the second cycle. The implementation of learning strategy of active knowledge sharing can improve questioning participation and learning outcomes of studying history subject of class XI IIS 1 in pre-cycle into the first cycle and from cycle I into cycle II. The students? questioning participation in pre-cycle was 21,88% which increased into 69,70% in the first cycle and 88,24% in the second cycle. The completeness of students? learning outcomes in pre-cycle was 76,47% which increased into 82,35% in the first cycle and succesfully developed into 94,12% in the second cycle.Based on the research findings and discussion, it can be drawn a conclusion that the learning strategy of active knowledge sharing can improve questioning participation and learning outcomes of studying history subject of class XI IIS 1 SMA Negeri 1 Boyolali.